Process profilling and characterization of puto oas from Albay, Bicol Region, Philippines - Tongson, Maria Clarissa C. (College of Home Economics, University of the Philippines Diliman, 2020)
Traditional foods are studied to preserve food and culture, provide product and process improvements, and form laws and regulations for quality and safety. The traditional food subject in this study is Puto Oas; a dry, half-circle shaped, toasted rice product from Oas, Albay. Its simple appearance hides the large impact it has brought to people’s livelihood and the municipality’s economy for generations. Said to have been conceptualized in 1915-1920s, the procedure in making Puto Oas brings insight to the producers’ ingenuity and resourcefulness to utilize large supplies of rice into a value-adding product that is unlike any other. The production process from one manufacturer each from Barangays Talongog and Mayao, were documented. Product dimensions, pH, water activity, proximate composition, APC, YMC and S. aureus count were obtained. Puto Oas is mainly composed of rice flour, sugar, and milk, with optional ingredients like vanilla flavoring, egg yolks, and margarine. The general process flow includes: (1) procurement of ingredients, (2) mixing, (3) sieving, (4) packing of the mixture into half- coconut husks and cutting, (5) steaming, (6) removal from the half coconuts and splitting into individual pieces, (7) roasting and toasting of individual pieces, (8) polishing and cooling, and lastly, (9) storage, transport, and distribution. The products are classified as low-acid (pH 5.74- 6.54) and low-water activity (aw 0.14-0.25), with proximate composition ranging from: 2.6-4.9% moisture, 86.6-87.5% total carbohydrates, 0.98-4.2% fat, 5.8-6.2% protein, 0.32-0.38% ash, and no detectable crude fiber. The two products differ greatly only in moisture and fat content, where the Mayao product has a higher moisture but a lower fat content than the Talongog product. Due to the products’ toasting step and low water activities, the presence of aerobic bacteria, yeasts, molds, and S. aureus was not detected, however, due to the nature of the product and it’s processing, untested microorganisms and toxins such as B. cereus and its toxin, Salmonella, and S. aureus enterotoxin may be present. The study brings forth initial information regarding the product, Puto Oas, and its production process. Further studies on shelf-life, in-process materials and equipment, and more microbiological tests are recommended in order to obtain more information on the product and its production process.